2004
DOI: 10.2519/jospt.2004.34.7.395
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Human Muscle Temperature Increases During 3-MHz Continuous and Pulsed Ultrasound With Equivalent Temporal Average Intensities

Abstract: Study Design: A repeated-measure crossover design was used. The independent variable was the type of ultrasound (pulsed or continuous) and the dependent variable was intramuscular temperature. Objective: To compare changes in intramuscular temperature resulting from the use of pulsed ultrasound versus continuous ultrasound with an equivalent spatial average temporal average (SATA) intensity. Background: There is a lack of research on the heat-generating capabilities of pulsed ultrasound within human muscle. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 16 publications
4
31
1
5
Order By: Relevance
“…A temperature increase of 2.8° C was noted in these in-vivo experiments. Using eqn (10) and using the exposure parameters of Gallo et al (2004) and the absorption coefficient of 0.26 Np/cm for human skeletal muscle, the predicted temperature increase is 2.5° C, which is consistent with their measured value of 2.8°C . Similarly, Carstensen et al (1990) measured the temperature elevation in rat liver exposed to 2.0-MHz continuous wave ultrasound with an I SATA of 0.57 W/cm 2 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A temperature increase of 2.8° C was noted in these in-vivo experiments. Using eqn (10) and using the exposure parameters of Gallo et al (2004) and the absorption coefficient of 0.26 Np/cm for human skeletal muscle, the predicted temperature increase is 2.5° C, which is consistent with their measured value of 2.8°C . Similarly, Carstensen et al (1990) measured the temperature elevation in rat liver exposed to 2.0-MHz continuous wave ultrasound with an I SATA of 0.57 W/cm 2 .…”
Section: Discussionsupporting
confidence: 77%
“…In one study, temperature rise was quantified in human muscle exposed to 3.0-MHz pulsed ultrasound with a spatial average, temporal average intensity of 0.5 W/cm 2 for 10 min (Gallo et al 2004). A temperature increase of 2.8° C was noted in these in-vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians chose a pulsed setting with the idea that it offers non-thermal tissue healing benefits, and no increase the tissue temperature. As stated by Gallo et al [10] the association of a pulsed ultrasound as strictly a non-thermal modality is an "oversimplification", and "is likely to be problematic in establishing appropriate dosages of pulsed ultrasound in clinical practice." Gallo et al has shown that a pulsed ultrasound does not always result in a non-thermal effect.…”
Section: Discussion Ultrasoundmentioning
confidence: 99%
“…Gallo et al has shown that a pulsed ultrasound does not always result in a non-thermal effect. He and his colleagues have indicated that ultrasound parameters set to 3MHz with a 50% duty cycle and a 1.0 W/cm 2 intensity for a period of 10 minutes had an equal effect on heating the tissue as did a 3MHz frequency with a 100% duty cycle and 0.5 W/cm 2 intensity, applied for 10 minutes [10]. In this example, the tissue was heated to approximately 3°C above baseline with both the continuous duty cycle and at 50%.…”
Section: Discussion Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation